O currículo como dispositivo biopolitico : uma análise das ciências humanas no ensino médio da BNCC/2017 - Waszkiewicz, Clóvis Lasta (2023)
This master's thesis aims at tracing the most important traces of the historical path taken by the human sciences in the Brazilian Secondary Education curriculum in the 20th century and the beginning 21th century. It will be done highlighting the relationship between human sciences curricula and the biopolitics formulations of Michel Foucault. We seek to understand how the Curriculum of Human Sciences in Secondary School acts as a Biopolitical dispositif. In addition, we resumed the concept of biopolitics based on texts by Foucault and some scholars related to Foucault's theory. Based on the characterization of biopolitics, we seek to identify the elaboration of the Human Sciences Curriculum from the BNCC (2017) and its role in constructing contemporary Brazilian citizenship. Finally, we elaborate possible connections between curriculum and biopolitics, seeking possibilities for criticism and resistance. At the beginning of the 20th century, the understanding of the Curriculum of Human Sciences became effective as an ally to two purposes: moral and religious formation, reduced to the containment of passions and sweetening of customs, and instrument for a scientific interpretation of society, a basis for the new management of bodies limited to Brazilian society at the time. In the second half of the 20th century, the Humanities continued to serve the government's biopolitical action, not only by defending the place of women as wives and mothers, but also by proposing that the acquisition of theories, concepts or knowledge, which dominated teaching until the 1960s, should give rise to the formation of certain modes of behavior and abilities in students, vital to market economy. We conclude the thesis stating that some historical traits of the secondary school curriculum of human sciences and the notion of competence and skill in the BNCC work as biopolitical operators that enable the government of the population